Algebra essay questions: A validated instrument for evaluating the students' higher-order thinking skills - Kania, Nia; Kyaruzi, Florence M.; Angraini, Lilis Marina (Universitas Sarjanawiyata Tamansiswa, 2023)
Indonesian pupils need help solving problems, particularly in mathematics, due to the need for practice questions with the higher-order thinking (HOT) type. This research aims to develop a reliable and valid tool for assessing students' higher-order thinking skills in mathematics. Developing a test involves gathering requirements, creating questions, assessing answers, running trials, analyzing data, making adjustments, and finally putting everything together. The instrument trial was conducted at SMAN at Majalengka, West Java. The total number of test subjects was 32 students. Research data were collected using a description test. The test instrument consists of 10 descriptions, but only 6 had good validity based on the value of V on the V-Aiken. In addition, the test package produces reliable questions based on Cronbach's Alpha scores. The test results of the instrument showed that the HOTS of mathematics for Grade X students was good. This step provides an overview to teachers in designing valid and relevant instruments.